The Effectiveness of Learning Media and Discourse Markers Mastery on Students’ Speaking Skill - Suryadi, Suryadi; Muhyidin, Asep; Syafrizal, Syafrizal; Erlangga, Fajar (PPSDP International Journal of Education, 2023)
Teachers must consider the most efficient use of speaking learning media in order to produce students with enhanced speaking skills through mastery of various discourse markers. This study examines the effectiveness of two speaking learning media, Scrabble Word (SW) and flashcards, among students with varying levels of discourse marker mastery. This quasi-experimental study employed a 2x2 factorial design. During the learning period, 100 students were divided into two groups and given SW or flashcards as instructional media. sampling technique using random sampling. Data was collected using tests of speaking ability and familiarity with various discourse markers. The results demonstrate that the speaking skills of students with varying degrees of DM mastery who use SW learning media are superior to those of students who use flashcard learning media. Students with a high level of discourse mastery and access to SW learning media demonstrated an improvement in their speaking abilities. This is evidenced by the values of Fo = 7.911 and Sig. 0.005<0.05; consequently, SW can be an effective and enjoyable tool for teaching speaking.